A new strain of Rhodococcus indonesiensis T22.7.1T and its functional potential for deacetylation of chitin and chitooligsaccharides - Xie, Junjie; Yin, Doudou; Ou, Junchao; Lu, Bo; Liao, Siming; Yang, Dengfeng; Zhang, Hongyan; Shen, Naikun (Frontiers in Microbiology, 2024)
Chitin is abundant in marine environments but is challenging to transform and utilize. A strain, T22.7.1T, with chitin deacetylation capabilities was isolated from the rhizosphere of Acanthus ebracteatus in the North Sea of China. Comparative 16S rDNA sequence analysis revealed that the new isolate had the highest sequence similarity (99.79%) with Rhodococcus indonesiensis CSLK01-03T, followed by R. ruber DSM 43338T, R. electrodiphilus JC435T, and R. aetherivorans 10bc312T (98.97%, 98.81%, and 98.83%, respectively). Further genome sequencing and phylogenetic analysis revealed that strain T22.7.1T is an R. indonesiensis species. However, based on additional taxonomic characterization, strain T22.7.1T is recognized as a novel type strain of R. indonesiensis different from CSLK01-03T. Following the first report of this new species in January 2024, this paper refines the taxonomic description of R. indonesiensis and investigates its application in converting chitin into chitosan. Through optimization, the chitin deacetylase (RiCDA) activity of strain T22.7.1T reached 287.02 U/mL, 34.88 times greater than that of the original enzyme (8.0 U/mL). Subsequently, the natural CDA enzyme was isolated and purified from the fermentation products with a purification factor of 31.83, and the specific activity of the enzyme solution reached 1200.33 U/mg. RiCDA demonstrated good pH and temperature adaptability and stability, as well as a wide range of substrate adaptabilities, with deacetylation effects on chitin, chitooligosaccharides, N-acetylglucosamine, etc. Product analysis showed that RiCDA treatment increased the deacetylation degree (DD) of natural chitin to 83%, which was superior to that of commercial chitosan. Therefore, RiCDA, as an excellent deacetylation tool for natural chitin and chitooligosaccharides, has great potential for application in the biorefining of natural polysaccharides.